2016
DOI: 10.4103/2229-516x.179016
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous leaf extract of Ocimum gratissimum improves hematological parameters in alloxan-induced diabetic rats via its antioxidant properties

Abstract: Objective:This study was designed to investigate the effects of Ocimum gratissimum (OG) on hematological parameters and oxidative stress in diabetic rats.Materials and Methods:Twenty-five male rats (150–200 g) were randomly grouped into five as control, normal + OG, diabetic untreated, diabetic + OG, and diabetic + glibenclamide groups. Diabetes was induced by 100 mg/kg of alloxan monohydrate in the diabetic untreated and diabetic + OG groups followed by treatment with distilled water and 400 mg/kg OG, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Change in weight of the testes, hearts, kidney, intestines and lungs of the rats were statistically insignificant. Data analysis of blood biochemical, haemotological and histopathological findings showed significant differences between control and treated groups and revealed that O. gratissimum essential oil is capable of invoking an inflammatory response that transits from acute to chronic on persistent administration [40]. While the study revealed that Ocimum oil might be better tolerated orally for systemic delivery, the oil has toxic potentialities that should not be overlooked [41].…”
Section: Discussionmentioning
confidence: 99%
“…Change in weight of the testes, hearts, kidney, intestines and lungs of the rats were statistically insignificant. Data analysis of blood biochemical, haemotological and histopathological findings showed significant differences between control and treated groups and revealed that O. gratissimum essential oil is capable of invoking an inflammatory response that transits from acute to chronic on persistent administration [40]. While the study revealed that Ocimum oil might be better tolerated orally for systemic delivery, the oil has toxic potentialities that should not be overlooked [41].…”
Section: Discussionmentioning
confidence: 99%
“…Ocimum gratissimum (OG) commonly called scent leaf is a dietary culinary spice used by different ethnic groups in Nigeria and other countries. It is called “Arurunta” by the Ukwuanis, “Ebe-amwonkho” in Edo, “Tchayo” in Fon, “Efinrin” in Yoruba, “Daidoya” in Hausa, “Nchuanwu” in Igbo, “Ntonng” in Ibibio, “Kunudiri” in Okrika and “Nunum’ in Akanb [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These constituents have been reported to possess several medicinal properties such as antibacterial activities [ 25 , 28 , 30 , 31 ] antidiabetic properties [ 27 ] and anti-hyperlipidemic effect [ 22 , 24 ]. Also, it was reported to improve blood parameters in experimental animals [ 23 , 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ocimum gratissimum (OG), planted in Nigeria for its nutritional and medicinal value, has been shown by several researchers to possess hypoglycaemic (Aguiyi et al ., 2000; Owoyele et al ., 2005; Egesie et al ., 2006) and antioxidant (Akinmoladun et al ., 2007; Aprioku & Obianime, 2008; Shittu et al ., 2016) properties. The hypoglycemic property was associated with inhibition of hepatic glycogen phosphorylase activity in streptozotocin-induced diabetic rats (Shittu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%